2018
DOI: 10.3390/pharmaceutics10040218
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes and Exosome-Inspired Vesicles for Targeted Drug Delivery

Abstract: The similarities between exosomes and liposomes, together with the high organotropism of several types of exosomes, have recently prompted the development of engineered-exosomes or exosome-mimetics, which may be artificial (liposomal) or cell-derived vesicles, as advanced platforms for targeted drug delivery. Here, we provide the current state-of-the-art of using exosome or exosome-inspired systems for drug delivery. We review the various approaches investigated and the shortcomings of each approach. Finally t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
363
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(367 citation statements)
references
References 177 publications
(303 reference statements)
2
363
0
2
Order By: Relevance
“…14 Exosomes are a type of micro vesicle secreted by cells, which can transfer internal substances to surrounding cells efficiently through rich adhesion proteins interacting with cell membrane. 27,28 Based on the above, we selected HFL-1 cells as the maternal cells for the source of exosomes, which were characterized by DLS and TEM; the results showed that the average particle size was 88.45 ± 19.53 nm, with uniform size and typical vesicular structure. The particle size of exosomes increased after ultrasonic loading, but the TEM showed that exosomes were still intact vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…14 Exosomes are a type of micro vesicle secreted by cells, which can transfer internal substances to surrounding cells efficiently through rich adhesion proteins interacting with cell membrane. 27,28 Based on the above, we selected HFL-1 cells as the maternal cells for the source of exosomes, which were characterized by DLS and TEM; the results showed that the average particle size was 88.45 ± 19.53 nm, with uniform size and typical vesicular structure. The particle size of exosomes increased after ultrasonic loading, but the TEM showed that exosomes were still intact vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…The possible role of EVs as an attractive source of drug delivery vehicles has been largely emphasized [119,120]. EVs present several advantages with respect to some similar drug delivery systems (i.e., polymeric nanoparticles and liposomes) [121], given that they produce limited systemic side effects, while being characterized by a great specificity [122]. The EVs' potential as drug carriers is inherent in their ability to deliver different types of cargoes, such as interfering RNA (siRNA) or pharmaceutically active molecules, even at long distances [123,124].…”
Section: Evs As Drug Carriersmentioning
confidence: 99%
“…As a result of all the advantages of liposomes as drug delivery systems (DDSs), several liposomal drug products are currently available in the market, such as Doxil V R , Ambisome V R , DaunoXome V R , Marqibo V R , Onivyde TM , Myocet V R , etc. (Antimisiaris et al, 2018), while others are under clinical testing, such as CPX-1, CPX-351, En-doTAG-1 (Lip-opack), LEP-ETU, etc. (Palazzolo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…(Palazzolo et al, 2018). Products like Doxil V R where the main pharmacological mechanism is passive targeting have poor selectivity toward cancer cells, which induce severe systemic side effects (Antimisiaris et al, 2018). To obtain active target ability in diseased sites, surface ligand modification of liposomes is mostly used in the literature .…”
Section: Introductionmentioning
confidence: 99%